At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

6x+6y=-6
5x+y=-13


*Substitution~ Please explain how on all steps shown


Sagot :

vivio
Solve for one variable in one of the equations:
5x + y = -13
y = -13 - 5x

plug that in for the variable in the other equation:
6x + 6y = -6
6x + 6 (-13 - 5x) = -6

Solve for the variable:
6x - 78 - 30x = -6
-24x - 78 = -6
-24x = 72
x = -3

Plug that in for the variable in any of the original equations:
5x + y = -13
5 (-3) + y = -13

Solve for the variable:
-15 + y = -13
y = 2

(-3, 2)